Clinical Utility of the Prenatal BACs-on-Beads™ Assay in Invasive Prenatal Diagnosis - Jiang, Yu; Wu, Lili; Ge, Yunshen; Zhang, Jian; Huang, Yanru; Wu, Qichang; Zhang, Yanhong; Zhou, Yulin (Frontiers in Genetics, 2022)
Background: The prenatal BACs-on-Beads™ (PNBoBs™) assay has been applied worldwide for prenatal diagnosis. However, there are neither guidelines nor consensus on choosing patients, sample types, or clinical pathways for using this technique. Moreover, different perspectives have emerged regarding its clinical value. This study aimed to evaluate its clinical utility in the context of clinical practice located in a prenatal diagnostic center in Xiamen, a city in southeast China. Methods: We tested 2,368 prenatal samples with multiple referral indications using both conventional karyotyping and PNBoBs™. Positive results from PNBoBs™ were verified using current gold-standard approaches. Results: The overall rates for the detection of pathogenic copy number variation (pCNV) by karyotyping and PNBoBs™ were 1.9% (46/2,368) and 2.0% (48/2,368), respectively. The overall detection rate of karyotyping combined with PNBoBs™ for pCNV was 2.3% (54/2,368). A total of 13 cases of copy number variation (CNV)with a normal karyotype were detected by PNBoBs™. Another case with a normal karyotype that was detected as a CNV of sex chromosomes by PNBoBs™ was validated to be maternal cell contamination by short tandem repeat analysis. Conclusion: Karyotyping combined with PNBoBs™ can improve both the yield and efficiency of prenatal diagnosis and is appropriate in the second trimester in all patients without fetal ultrasound anomalies who undergo invasive prenatal diagnosis.